Prevalence of depression, anxiety and stress among non-clinical workers in Columbia Asia Hospital - Jamal, Fazlina (Universiti Sains Malaysia, 2015)
Few studies conducted before, has reported on the prevalence of depression, anxiety and stress among clinical workers. However, only a fewer study reported on psychological distress among non-clinical workers. This study is aimed to determine the prevalence of depression anxiety and stress among non-clinical workers and factors that associated with it. A total of 63 non-clinical workers take part and completed the DASS 42 questionnaire as well as demographic form. The prevalence of moderate, severe and extremely severe level of depression anxiety and stress were 12.7%, 30.2% and 8% respectively. Depression was significantly associated with exposure toward sexual harassment and bully, communication problem among co-workers and superior and tight deadlines. Anxiety was significantly related to exposure toward hazardous environment during working hours, sexual harassment, race and gender discrimination, communication problem and rate of salary received put workers under pressure. Stress was significantly associated with communication problem, threat of job loss and rate of salary received put workers under pressure. Therefore, above all factors listed, the prevalence of anxiety level among non-clinical workers is the highest compared with depression or stress level.